Political stasis or protectionist rut?: Policy mechanisms for trade reform in a democracy - Emily J. Blanchard; Gerald Willmann (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper analyzes the dynamics of trade policy reform under democracy. In an overlapping generations model, heterogeneous agents may acquire skills when young, thereby determining the skill composition of their cohort. Current and anticipated trade policies influence education decisions, and thus the identity of the median voter. We show that there may exist two political steady states: one protectionist and one liberal. Transition from the former to the latter can be achieved by government announcements, temporary educational subsidies, or (exogenous) tariff liberalization by trading partners, but not, in general, by transfer payments to adversely affected workers. We find additionally that reform is politically feasible only if the proposed liberalization is sufficiently large, suggesting that radical reform may be necessary for escaping a protectionist rut.
Keywords: D72; E60; F13; F16; 330; Außenhandelsliberalisierung; Public Choice; Overlapping Generations; Theorie